HAK ASASI MANUSIA: HAK ASASI MANUSIA - Annisa Rachmawati; Delyarachmadani Wardjony Putri; Marsha Anastasya; Nabila, Syahwa (Amal Insani Foundation, 2024)
This paper discusses the human rights based on the historical and legal standpoint. Historically, the human rights struggle in Indonesia appears during period the indegenous people against to oppression of the Colonial. The struggle to get independence essentially was the human rights enforcement. Legally, the human rights in Indonesia have the law basis through Ketetapan MPR no. XVII/MPR/ 1998 on Human Rights, and Undang Undang No. 39/ 2000 on Human Rights.